2020
DOI: 10.1029/2019jb019093
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Clinopyroxene‐NaCl‐H2O System at High Temperatures and Pressures: Implications for High‐Conductivity Anomalies in the Deep Crust and Subduction Zone

Abstract: Electrical conductivities of the clinopyroxene (Cpx)-NaCl-H 2 O system with various salinities (5, 10, 15, 20, 25 wt%) and fluid fractions (5, 10, 15, 20, 25 vol%) were measured at 1 GPa and 673-973 K. For comparison with electrical properties of the Cpx-NaCl-H 2 O system, the conductivities of dry Cpx, hydrous Cpx, and a Cpx-H 2 O system were researched at the same temperature and pressure. The experimental results included (1) the electrical conductivities of all samples that were associated with Cpx and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…In addition to geometry, the composition of the aqueous fluid is important for electrical conductivity (Reynard, 2016; Reynard et al, 2011). NaCl is thought to be the critical solute for aqueous liquids originated from a variety of geological environments, which was widely studied by both experiments and calculations (H. Guo & Keppler, 2019; X. Guo et al, 2015; Sakuma & Ichiki, 2016; Shimojuku et al, 2014, 2012; Sinmyo & Keppler, 2017; Sun et al, 2020). In addition, the NaCl‐bearing aqueous fluids was also thought to control the electrical conductivity for albite‐NaCL‐H 2 O, albite‐(quartz)‐H 2 O (X. Guo et al, 2015), plagioclase‐NaCl‐H 2 O (Li et al, 2018), and clinopyroxene‐NaCl‐H 2 O system (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to geometry, the composition of the aqueous fluid is important for electrical conductivity (Reynard, 2016; Reynard et al, 2011). NaCl is thought to be the critical solute for aqueous liquids originated from a variety of geological environments, which was widely studied by both experiments and calculations (H. Guo & Keppler, 2019; X. Guo et al, 2015; Sakuma & Ichiki, 2016; Shimojuku et al, 2014, 2012; Sinmyo & Keppler, 2017; Sun et al, 2020). In addition, the NaCl‐bearing aqueous fluids was also thought to control the electrical conductivity for albite‐NaCL‐H 2 O, albite‐(quartz)‐H 2 O (X. Guo et al, 2015), plagioclase‐NaCl‐H 2 O (Li et al, 2018), and clinopyroxene‐NaCl‐H 2 O system (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory-based constraints on the electrical conductivity of fluids have provided valuable insight into the fluid-driven processes in the subduction zone and overlying mantle wedge 23 , 24 . The experimental constraints on the electrical conductivity of aqueous fluid include pure water 25 , 26 , aqueous fluids released by dehydration 23 , 24 , 27 , 28 and saline aqueous fluids with varying salinities 29 34 . However, the effect of both carbon and hydrogen bearing (C–H–O) aqueous fluids on electrical conductivity remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Saline ions (Na + and Cl − ) in aqueous fluids are released from subduction slabs during dehydration and metasomatism (Reynard, 2016;Förster et al, 2019;Manthilake et al, 2021b). Numerous studies have attributed the origin of the high-conductivity anomalies in the mid-lower crust and some subduction zones to the distribution of NaClbearing aqueous fluids along the grain boundaries of silicate minerals (Shimojuku et al, 2012(Shimojuku et al, , 2014Guo et al, 2015;Sinmyo and Keppler, 2017;Li et al, 2018;Sun et al, 2020). However, the effect of saline fluids on the electrical conductivity of silicate minerals in mantle wedge regions remains poorly constrained.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2019) recently demonstrated that NaCl-bearing aqueous fluids might be interconnected in mantle wedges. The electrical conductivities of clinopyroxene (Cpx)-NaCl-H 2 O, plagioclase (Pl)-NaCl-H 2 O, albite (Ab)-NaCl-H 2 O and pure NaCl-bearing saline fluid systems have been previously investigated (Guo et al, 2015;Li et al, 2018;Guo and Keppler, 2019;Sun et al, 2020), but the electrical conductivity of saline fluid-bearing olivine aggregates has not been reported. Although saline fluids exert a dominant control over the conductivities of saline fluid-bearing mineral aggregates, the mineral species still play a significant role in the system conductivity as a whole (Guo et al, 2015;Li et al, 2018;Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation